2010
DOI: 10.1186/1471-2334-10-339
|View full text |Cite
|
Sign up to set email alerts
|

Social and cultural features of cholera and shigellosis in peri-urban and rural communities of Zanzibar

Abstract: BackgroundResponding to the high burden of cholera in developing countries, the WHO now considers vaccination as a supplement to the provision of safe drinking water and improved sanitation in the strategy for cholera control in endemic settings. Cultural concepts of illness affect many aspects of public health. In the first step of a two-step strategy to examine determinants of cholera vaccine acceptance, this study identified social and cultural features of diarrhoeal illness for cholera control in endemic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
51
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 22 publications
5
51
1
Order By: Relevance
“…Our study assessed the knowledge of, attitudes toward, and prevention practices relating to cholera among urban slum-dwellers. We found that only 27% of the respondents could identify cholera as watery diarrhoea, which was lower than that observed in studies in Dhaka, Bangladesh, Zanzibar and Haiti where 60-89% of the population could characterize cholera as watery stool or diarrhoea (Schaetti et al, 2010), Rochars et al, 2010). Definition of cholera varies in many documents including WHO.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Our study assessed the knowledge of, attitudes toward, and prevention practices relating to cholera among urban slum-dwellers. We found that only 27% of the respondents could identify cholera as watery diarrhoea, which was lower than that observed in studies in Dhaka, Bangladesh, Zanzibar and Haiti where 60-89% of the population could characterize cholera as watery stool or diarrhoea (Schaetti et al, 2010), Rochars et al, 2010). Definition of cholera varies in many documents including WHO.…”
Section: Discussioncontrasting
confidence: 50%
“…Our study and other studies from Bangladesh and Zanzibar showed that urban and peri-urban people are more likely to give ORS to patients primarily for the treatment of cholera than the rural people (Schaetti et al, 2010).…”
Section: Discussionmentioning
confidence: 73%
“…3,4 The results presented here are based on descriptive findings from a previous report that clarified similarities and differences of community views of cholera in the peri-urban and rural target populations in Zanzibar. 23 This study aimed to assess social and cultural determinants of anticipated oral cholera vaccine acceptance prior to a mass vaccination campaign in a peri-urban and a rural community of Zanzibar. Because of the reported high awareness of cholera in the study communities, 23 it was hypothesized that anticipated acceptance of the free vaccine would also be high, and that determinants of anticipated acceptance would not only include sociodemographic and economic characteristics, especially for high-priced vaccines, [24][25][26] but also socio-cultural features of illness.…”
mentioning
confidence: 99%
“…23 This study aimed to assess social and cultural determinants of anticipated oral cholera vaccine acceptance prior to a mass vaccination campaign in a peri-urban and a rural community of Zanzibar. Because of the reported high awareness of cholera in the study communities, 23 it was hypothesized that anticipated acceptance of the free vaccine would also be high, and that determinants of anticipated acceptance would not only include sociodemographic and economic characteristics, especially for high-priced vaccines, [24][25][26] but also socio-cultural features of illness. Social and cultural determinants of anticipated OCV acceptance were investigated with regard to the OCV at no cost, and at three distinct price levels.…”
mentioning
confidence: 99%
“…Witchcraft and God's will as perceived causes of cholera were also reported by other studies. This study highlights the need to incorporate social and cultural issues related to cholera in health promotion messages and materials in addition to messages addressing traditional biomedical risk factors [17][18][19].…”
Section: Discussionmentioning
confidence: 99%